A method for preparing a high-nitrogen denitration adsorbent formulation

CN122912801APending Publication Date: 2026-10-16HANGZHOU YONGSHENG ACTIVATOR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610901571.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-22
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,现有技术中将氟硅酸柱撑与有机柱撑复合使用时,常面临以下难题:(1)白土活化需要300℃以上高温,而有机季铵盐在超过200℃时易分解,传统“一步法”或“高温复合”会导致有机组分失效;(2)氟硅酸反应生成的MgF2、CaF2等难溶氟化物残留,易腐蚀设备,逸出HF,且干扰后续有机柱撑;(3)传统分子印迹需要聚合交联和索氏提取,难以工业化;(4)缺乏简单有效的方法在膨润土层间构筑尺寸匹配的限域空间

Benefits of technology

1. 本发明通过铝酸洗涤-去离子水洗涤两步法对氟硅酸柱撑后的膨润土进行除氟处理,在有效去除氟离子的同时,同步引入铝柱撑组分,一方面避免了氟化物残留对设备的腐蚀及对后续有机柱撑的干扰,另一方面利用Al3+离子交换在膨润土层间构建了额外的Lewis酸位点和稳定的层间柱结构,显著增大了吸附剂的比表面积和微孔孔容。在此基础上,依次引入碱性氮模板分子进行预吸附、季铵盐进行有机柱撑、正硅酸乙酯在弱碱条件下水解缩聚,形成包裹模板分子的纳米限域硅氧网络;后续通过低温溶剂萃取温和脱除模板分子,在膨润土层间留下了尺寸与碱性氮分子精准匹配的“分子印迹”空穴。TEOS交联形成的Si-O-Si网络赋予该限域空间优异的刚性和热稳定性,有效避免了常规有机硅柱撑膨润土在干燥、再生过程中层间距塌陷的问题,从而大幅提升了对碱性氮化物的吸附容量和选择性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application belongs to the technical field of petroleum refining adsorbent, and particularly relates to a preparation method of a high-nitrogen-content denitrogenation adsorbent. First, activated composite powder A is obtained by acid activation and calcination of white clay and diatomite; then, aluminum fluoride-composite pillared bentonite filter cake is obtained by removing fluorine and simultaneously introducing aluminum pillaring through two-step fluorine removal of sodium-based bentonite after fluorosilicic acid pillaring reaction and washing with aluminate and deionized water; then, modified bentonite B is obtained by adding alkaline nitrogen template molecules pre-adsorption, quaternary ammonium salt organic pillaring and tetraethyl orthosilicate hydrolysis and polycondensation in sequence to form a nano-limited silicon-oxygen network wrapping the template molecules, and then by low-temperature vacuum drying; finally, the modified bentonite B is mixed with the activated composite powder A, neutral silica sol is added, and the mixture is extruded into a strip, and then the template molecules are removed by low-temperature solvent extraction and vacuum step drying, and the adsorbent is obtained. The adsorbent has a large specific surface area, high adsorption capacity, good selectivity and easy regeneration, and is suitable for deep denitrogenation of petroleum distillates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of petrochemical refining adsorbent technology, specifically relating to a method for preparing a high-nitrogen-content denitrification adsorbent formulation. Background Technology

[0002] In petrochemical production, basic nitrogen compounds (such as pyridine, quinoline, aniline and their derivatives) are commonly found in reformate, catalytic diesel, and biodiesel fractions. These substances can easily lead to catalyst poisoning and deactivation in subsequent processing, while also affecting the color and safety of the oil.

[0003] Existing denitrification technologies mainly include hydrorefining, acid washing, or adsorption. Hydrorefining involves large investments and high hydrogen consumption; acid washing generates a large amount of waste acid; while adsorption methods (such as activated clay, activated carbon, and modified molecular sieves) are simple to operate, they suffer from prominent problems such as low adsorption capacity, poor selectivity, and difficulty in regeneration. Especially for raw materials with high nitrogen content, existing adsorbents have rapid penetration and short lifespan, making it difficult to meet the requirements of deep industrial denitrification.

[0004] In recent years, modified bentonite has been extensively studied due to its layered structure and ion exchange properties. Fluorosilicic acid pillars can introduce Lewis acid sites into the layers, while organic quaternary ammonium salt pillars can expand the interlayer spacing and create a hydrophobic environment. However, when using fluorosilicic acid pillars in combination with organic pillars in the existing technology, the following problems are often encountered: (1) Activation of bentonite requires a high temperature of over 300°C, while organic quaternary ammonium salts are easily decomposed at temperatures above 200°C. Traditional "one-step method" or "high-temperature composite" will lead to the failure of organic components; (2) The residual insoluble fluorides such as MgF2 and CaF2 generated by the reaction of fluorosilicic acid are easy to corrode equipment, release HF, and interfere with subsequent organic pillars; (3) Traditional molecular imprinting requires polymerization crosslinking and Soxhlet extraction, which is difficult to industrialize; (4) There is a lack of simple and effective methods to construct a size-matched confined space between bentonite layers.

[0005] Therefore, developing a high-capacity, highly selective, easily regenerable, and easily industrialized denitrification adsorbent has significant market value. Summary of the Invention

[0006] The purpose of this invention is to address existing problems by providing a method for preparing a high-nitrogen-content denitrification adsorbent formulation.

[0007] This invention is achieved through the following technical solution: A method for preparing a high-nitrogen-content denitrification adsorbent formulation includes the following steps: S1. After kneading white clay and diatomaceous earth with dilute acid and deionized water, they are calcined and activated at 300~400℃ to obtain activated composite powder A. S2. Disperse sodium-based bentonite in deionized water to prepare a 5-15 wt% slurry, and add fluorosilicic acid to carry out a pillaring reaction. After the reaction, fluoride ions were removed by a two-step method of aluminic acid washing and deionized water washing, and aluminum pillar components were introduced simultaneously. Each washing was carried out using a pulping-pressure filtration cycle process until the fluoride ion concentration in the washing liquid was ≤100ppm, and aluminum / fluorosilicic acid composite pillar bentonite filter cake was obtained. S3. The filter cake obtained in step S2 is redispersed in deionized water to prepare a slurry of 5-15 wt%. Alkaline nitrogen template molecules are added sequentially for pre-adsorption, followed by the addition of quaternary ammonium salt for organic pillaring, and tetraethyl orthosilicate (TEOS) as a crosslinking curing agent. Under weakly alkaline conditions, hydrolysis and polycondensation are carried out to form a nano-confined silicon-oxygen network that encapsulates template molecules between the bentonite layers. Then, the mixture is filtered, washed with hot water, and dried under low temperature vacuum to obtain modified bentonite B. S4. Mix modified bentonite B with activated composite powder A, add neutral silica sol as a binder, add deionized water to adjust to a state suitable for extrusion, extrude into strips with a diameter of 1~5mm, and after molding, first remove template molecules by low-temperature solvent extraction, and then dry in steps under vacuum to obtain the adsorbent formulation.

[0008] Further, the mass ratio of white clay to diatomaceous earth in step S1 is (2~4):1; The dilute acid is dilute sulfuric acid, with a concentration of 2-5%, and the amount of dilute sulfuric acid added is 3-8% of the total mass of the clay and diatomaceous earth. The amount of deionized water added is 15-25% of the total mass of the clay and diatomaceous earth.

[0009] Further, the concentration of fluorosilicic acid in step S2 is 15-25%, and the amount added is 10-20% of the dry weight of sodium-based bentonite; The reaction temperature is 60~90℃, and the reaction time is 2~6h.

[0010] Further, the aluminate washing in step S2 specifically involves: using an aluminum sulfate solution with a concentration of 0.5-2.0%, adjusting the pH to 2.5-3.5 with dilute sulfuric acid, maintaining a liquid-to-solid ratio of (4-6):1 during washing, and stirring for 30-60 minutes; this step also has the following functions: dissolving and complexing fluorides (generating AlF6). 3- ), through Al 3+ Ion exchange enters the bentonite interlayer to form aluminum pillars and regulate the interlayer acidity; Then wash with deionized water at a liquid-to-solid ratio of (4~6):1, stirring for 10~20 minutes, and wash 2~3 times.

[0011] Furthermore, the basic nitrogen template molecule mentioned in step S3 is pyridine; The amount of template molecule used is 2-4% of the dry weight of bentonite, and pre-adsorption is carried out by stirring at room temperature for 30-60 minutes.

[0012] Further, the quaternary ammonium salt mentioned in step S3 is hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride; The amount of the quaternary ammonium salt is 8-15% of the dry weight of bentonite, and the mixture is heated to 50-70℃ and stirred for 1-3 hours to form an organic pillar.

[0013] Furthermore, in step S3, the amount of tetraethyl orthosilicate (TEOS) is 5-15% of the dry weight of bentonite. After adding TEOS, the pH of the slurry is adjusted to 7.5-8.5 with dilute ammonia water, and the mixture is stirred and hydrolyzed at 40-60°C for 2-6 hours to form a cross-linked Si-O-Si network between and on the surface of the bentonite layers, thus "locking" the template molecules in confined vacancies.

[0014] Further, the hot water washing in step S3 specifically involves washing the pulp with hot water at 40~80℃ 1~3 times, with a liquid-to-solid ratio of (3~6):1; Drying is performed under vacuum at 40~80℃.

[0015] Further, in step S4, the mass ratio of modified bentonite B to activated composite powder A is (3~6):1; The neutral silica sol has a solid content of 20-40%, a pH of 6.5-7.5, and is used in an amount of 1-5% of the total mass of the mixed powder.

[0016] Further, the low-temperature solvent extraction to remove template molecules in step S4 specifically involves: immersing the extruded material in a mixed solvent of anhydrous ethanol and deionized water (volume ratio (1~3):1), stirring and extracting at 40~60℃ 2~4 times, 30~60 min each time, until template molecules are no longer detectable in the extract; The extraction conditions are mild and do not damage the quaternary ammonium salt pillar and TEOS crosslinking network, while completely removing template molecules and forming size-matched nitridation adsorption sites.

[0017] Further, the vacuum stepwise drying in step S4 specifically involves: firstly drying at 80~100℃ and at atmospheric pressure or -0.02~-0.04MPa for 0.5~1h; The second step involves drying at 100~120℃ and a vacuum of -0.08~-0.095MPa for 1~2 hours.

[0018] The adsorbent formulation prepared by the method is used in the denitrification and decolorization of oil products in the petrochemical field.

[0019] The present invention has the following advantages over the prior art: 1. This invention employs a two-step method—aluminate washing followed by deionized water washing—to defluorinate bentonite after fluorosilicate pillaring. This effectively removes fluoride ions while simultaneously introducing aluminum pillaring components. This avoids corrosion of equipment by residual fluorides and interference with subsequent organic pillaring processes. Furthermore, it utilizes Al… 3+ Ion exchange constructs additional Lewis acid sites and a stable interlayer pillar structure within the bentonite layers, significantly increasing the specific surface area and micropore volume of the adsorbent. Based on this, basic nitrogen template molecules are sequentially introduced for pre-adsorption, quaternary ammonium salts are used for organic pillaring, and tetraethyl orthosilicate is hydrolyzed and polycondensed under weakly alkaline conditions to form a nano-confined silicon-oxygen network encapsulating the template molecules. Subsequently, the template molecules are gently removed by low-temperature solvent extraction, leaving "molecular imprint" cavities in the bentonite interlayers with dimensions precisely matched to the basic nitrogen molecules. The Si-O-Si network formed by TEOS crosslinking endows this confined space with excellent rigidity and thermal stability, effectively avoiding the interlayer collapse problem encountered by conventional organosilicon-pillared bentonite during drying and regeneration, thereby significantly improving the adsorption capacity and selectivity for basic nitrogen compounds.

[0020] 2. This invention combines modified bentonite with a composite powder of kaolin and diatomaceous earth activated and calcined with dilute acid, and uses neutral silica sol as a binder for extrusion molding. Combined with a vacuum stepwise drying process, the prepared adsorbent formulation possesses high specific surface area, suitable pore size distribution, and good mechanical strength. The static adsorption capacity can reach over 45 mg / g. Compared with existing technologies, this invention overcomes the problems of low capacity, poor selectivity, difficult regeneration, and fluorine residue caused by fluorosilicate pillars in traditional adsorbents. It also solves the process contradiction of easy high-temperature decomposition of organic components in organic-inorganic composite pillars. The entire method is simple to operate and easy to industrialize, showing significant application prospects in the deep denitrification and decolorization treatment of petroleum fractions such as reformed feedstocks and catalytic diesel. Detailed Implementation

[0021] To further explain the present invention, the following specific embodiments are described.

[0022] Example 1 A method for preparing a high-nitrogen-content denitrification adsorbent formulation includes the following steps: S1. White clay and diatomaceous earth are kneaded together with dilute sulfuric acid and deionized water at a mass ratio of 2:1 and then calcined and activated at 300℃ to obtain activated composite powder A. The concentration of the dilute sulfuric acid is 2%, and the amount of dilute sulfuric acid added is 3% of the total mass of the clay and diatomaceous earth. The amount of deionized water added is 15% of the total mass of the clay and diatomaceous earth; S2. Disperse sodium-based bentonite in deionized water to prepare a 5wt% slurry, add 15% fluorosilicic acid to carry out a pillaring reaction at a temperature of 60℃ for 2 hours. The amount of fluorosilicic acid added is 10% of the dry weight of sodium-based bentonite; After the reaction was complete, a 0.5% aluminum sulfate solution was used, and the pH was adjusted to 2.5 with dilute sulfuric acid. The liquid-to-solid ratio during washing was 4:1, and the stirring time was 30 minutes. This step also serves the following functions: dissolving and complexing fluorides (to generate AlF6). 3- ), through Al 3+ Ion exchange enters the bentonite interlayer to form aluminum pillars and adjust the interlayer acidity. Then, it is washed with deionized water at a liquid-to-solid ratio of 4:1 and a stirring time of 10 min. The washing is repeated twice, and the aluminum pillar components are introduced simultaneously. Each washing adopts a pulping-press filtration circulation process until the fluoride ion concentration of the washing liquid is ≤100ppm, and aluminum / fluorosilicic acid composite pillar bentonite filter cake is obtained. S3. The filter cake obtained in step S2 is redispersed in deionized water to prepare a 5wt% slurry. Alkaline nitrogen template molecules are added sequentially, and the mixture is stirred at room temperature for 30 minutes for pre-adsorption. The amount of template molecules used is 2% of the dry weight of bentonite. Then add hexadecyltrimethylammonium bromide, heat to 50°C and stir for 1 hour to form an organic pillar. The amount of hexadecyltrimethylammonium bromide is 8% of the dry weight of bentonite. Tetraethyl orthosilicate (TEOS) is added as a crosslinking curing agent. The amount of TEOS is 5% of the dry weight of bentonite. After adding TEOS, the pH of the slurry is adjusted to 7.5 with dilute ammonia. The slurry is stirred and hydrolyzed at 40°C for 2 hours to form a crosslinked Si-O-Si network between and on the surface of the bentonite layers, which "locks" the template molecules in the confined vacancies. Then filter, slurry and wash once with 40℃ hot water, with a liquid-to-solid ratio of 3:1, and then dry at low temperature and vacuum at 40℃ to obtain modified bentonite B; S4. Modified bentonite B and activated composite powder A are mixed at a mass ratio of 3:1, and neutral silica sol is added as a binder. The neutral silica sol has a solid content of 20%, a pH of 6.5, and is used at 1% of the total mass of the mixed powder. Add deionized water to adjust to the extrudable state, extrude into strips with a diameter of 1 mm, and after forming, immerse the extruded material in a mixed solvent of anhydrous ethanol and deionized water (volume ratio 1:1), and extract twice at 40°C for 30 min each time, until template molecules are not detectable in the extract. After vacuum stepwise drying, the adsorbent preparation is obtained; The vacuum stepwise drying process specifically involves the following steps: First, drying at 80°C and normal pressure for 0.5 hours; The second step involves drying at 100℃ and a vacuum of -0.08MPa for 1 hour.

[0023] Example 2 A method for preparing a high-nitrogen-content denitrification adsorbent formulation includes the following steps: S1. White clay and diatomaceous earth are kneaded together with dilute sulfuric acid and deionized water at a mass ratio of 3:1 and then activated by calcination at 350℃ to obtain activated composite powder A. The concentration of the dilute sulfuric acid is 3.5%, and the amount of dilute sulfuric acid added is 5.5% of the total mass of the clay and diatomaceous earth. The amount of deionized water added is 20% of the total mass of the clay and diatomaceous earth; S2. Disperse sodium-based bentonite in deionized water to prepare a 10wt% slurry, add 20% fluorosilicic acid to carry out a pillaring reaction at a temperature of 75℃ for 4 hours. The amount of fluorosilicic acid added is 15% of the dry weight of sodium-based bentonite; After the reaction was complete, a 1.0% aluminum sulfate solution was used, and the pH was adjusted to 3 with dilute sulfuric acid. The liquid-to-solid ratio during washing was 5:1, and the stirring time was 45 min. This step also serves the following functions: dissolving and complexing fluorides (generating AlF6). 3- ), through Al 3+ Ion exchange enters the bentonite interlayer to form aluminum pillars and adjust the interlayer acidity. Then, it is washed with deionized water at a liquid-to-solid ratio of 5:1 and a stirring time of 15 min. The washing is repeated twice, and the aluminum pillar component is introduced simultaneously. Each washing adopts a pulping-press filtration circulation process until the fluoride ion concentration of the washing liquid is ≤100ppm, and aluminum / fluorosilicic acid composite pillar bentonite filter cake is obtained. S3. The filter cake obtained in step S2 is redispersed in deionized water to prepare a 10wt% slurry. Alkaline nitrogen template molecules are added sequentially, and the mixture is stirred at room temperature for 45 minutes for pre-adsorption. The amount of template molecules used is 3% of the dry weight of bentonite. Then add hexadecyltrimethylammonium bromide, heat to 60°C and stir for 2 hours to form an organic pillar. The amount of hexadecyltrimethylammonium bromide is 11% of the dry weight of bentonite. Tetraethyl orthosilicate (TEOS) is added as a crosslinking curing agent. The amount of TEOS is 10% of the dry weight of bentonite. After adding TEOS, the pH of the slurry is adjusted to 8.0 with dilute ammonia. The slurry is stirred and hydrolyzed at 50°C for 4 hours to form a crosslinked Si-O-Si network between and on the surface of the bentonite layers, which "locks" the template molecules in the confined vacancies. Then, it was filtered, slurried and washed twice with hot water at 60℃, with a liquid-to-solid ratio of 4.5:1, and then dried under low temperature vacuum at 60℃ to obtain modified bentonite B. S4. Modified bentonite B and activated composite powder A are mixed at a mass ratio of 4.5:1, and neutral silica sol is added as a binder. The neutral silica sol has a solid content of 30%, a pH of 7.0, and is used at 3% of the total mass of the mixed powder. Add deionized water to adjust to the extrudable state, extrude into strips with a diameter of 3mm, and after forming, immerse the extruded material in a mixed solvent of anhydrous ethanol and deionized water (volume ratio 2:1), and extract three times at 50℃ for 45min each time, until template molecules are not detectable in the extract. After vacuum stepwise drying, the adsorbent preparation is obtained; The vacuum stepwise drying process specifically involves the following steps: First, drying at 90°C and normal pressure for 0.7 hours. The second step involves drying at 110℃ and a vacuum of -0.085MPa for 1.5 hours.

[0024] Example 3 A method for preparing a high-nitrogen-content denitrification adsorbent formulation includes the following steps: S1. White clay and diatomaceous earth are kneaded together with dilute sulfuric acid and deionized water at a mass ratio of 4:1 and then calcined and activated at 400℃ to obtain activated composite powder A. The concentration of the dilute sulfuric acid is 5%, and the amount of dilute sulfuric acid added is 8% of the total mass of the clay and diatomaceous earth. The amount of deionized water added is 25% of the total mass of the clay and diatomaceous earth; S2. Disperse sodium-based bentonite in deionized water to prepare a 15wt% slurry, add 25% fluorosilicic acid to carry out a pillaring reaction at a reaction temperature of 90℃ for 6 hours. The amount of fluorosilicic acid added is 20% of the dry weight of sodium-based bentonite; After the reaction was complete, a 2.0% aluminum sulfate solution was used, and the pH was adjusted to 3.5 with dilute sulfuric acid. The liquid-to-solid ratio during washing was 6:1, and the stirring time was 60 minutes. This step simultaneously serves the following functions: dissolving and complexing fluorides (generating AlF6). 3- ), through Al 3+ Ion exchange enters the bentonite interlayer to form aluminum pillars and adjust the interlayer acidity. Then, it is washed with deionized water at a liquid-to-solid ratio of 6:1 and a stirring time of 20 min. The washing is repeated 3 times, and the aluminum pillar component is introduced simultaneously. Each washing adopts a pulping-press filtration circulation process until the fluoride ion concentration of the washing liquid is ≤100ppm, and aluminum / fluorosilicic acid composite pillar bentonite filter cake is obtained. S3. The filter cake obtained in step S2 is redispersed in deionized water to prepare a 15wt% slurry. Alkaline nitrogen template molecules are added sequentially, and the mixture is stirred at room temperature for 60 minutes for pre-adsorption. The amount of template molecules used is 4% of the dry weight of bentonite. Then add hexadecyltrimethylammonium bromide, heat to 70°C and stir for 3 hours to form an organic pillar. The amount of hexadecyltrimethylammonium bromide is 15% of the dry weight of bentonite. Tetraethyl orthosilicate (TEOS) is added as a crosslinking curing agent. The amount of TEOS is 15% of the dry weight of bentonite. After adding TEOS, the pH of the slurry is adjusted to 8.5 with dilute ammonia. The slurry is stirred and hydrolyzed at 60°C for 6 hours to form a crosslinked Si-O-Si network between and on the surface of the bentonite layers, which "locks" the template molecules in the confined vacancies. Then, it was filtered, pulped and washed three times with hot water at 80℃, with a liquid-to-solid ratio of 6:1, and then dried under low temperature vacuum at 80℃ to obtain modified bentonite B. S4. Modified bentonite B and activated composite powder A are mixed at a mass ratio of 6:1, and neutral silica sol is added as a binder. The neutral silica sol has a solid content of 40%, a pH of 7.5, and is used at 5% of the total mass of the mixed powder. Add deionized water to adjust to the extrusion state, extrude into strips with a diameter of 5mm, and after forming, immerse the extruded material in a mixed solvent of anhydrous ethanol and deionized water (volume ratio 3:1), and extract by stirring at 60℃ 4 times, 60min each time, until template molecules are not detected in the extract. After vacuum stepwise drying, the adsorbent preparation is obtained; The vacuum stepwise drying process specifically involves: first, drying at 100°C and normal pressure for 1 hour; The second step involves drying at 120℃ and a vacuum of -0.095MPa for 2 hours.

[0025] Comparative Example 1 Compared with Example 2, Comparative Example 1 omits the pyridine template molecule pre-adsorption step in step S3, while the remaining steps and parameters are the same as in Example 2.

[0026] Comparative Example 2 Compared with Example 2, Comparative Example 2 does not include TEOS in step S3, but only performs template pre-adsorption and quaternary ammonium salt organic pillaring. The remaining steps and parameters are the same as in Example 2.

[0027] Comparative Example 3 Compared with Example 2, in Comparative Example 3, the aluminate washing step is omitted in step S2, and only deionized water is used for washing to remove fluoride. The remaining steps and parameters are the same as in Example 2.

[0028] Comparative Example 4 Compared with Example 2, Comparative Example 4 omits both pyridine template pre-adsorption and TEOS addition in step S3, while the remaining steps and parameters are the same as in Example 2.

[0029] Comparative Example 5 Compared with Example 2, Comparative Example 5 uses an equal amount of activated clay (specific surface area ≥200m²) in step S4. 2 / g) replace activated composite powder A, and the remaining steps and parameters are the same as in Example 2.

[0030] 1. Experimental testing 1.1 Specific surface area test The specific surface area of ​​the adsorbent was determined by nitrogen adsorption-desorption (BET method), and the test results are shown in Table 1.

[0031] Table 1

[0032] As shown in Table 1 above, the specific surface areas of Examples 2 and 3 are superior to those of the comparative examples, while Comparative Example 3 has the lowest specific surface area. This indicates that aluminate washing, while removing fluoride, also effectively removes Al... 3+ The aluminum pillars formed in the interlayer increase the interlayer spacing and the proportion of micropores. The specific surface areas of Comparative Examples 1 and 2 are both lower than those of Example 2, confirming that the pyridine template and TEOS crosslinking not only construct confined holes at the molecular level, but also effectively prevent the collapse of the interlayer spacing during high-temperature drying through the Si-O-Si network.

[0033] 1.2 Static Adsorption Test Weigh 0.5 g of the adsorbent preparation and add it to 50 mL of simulated oil (model oil with a basic nitrogen content of 1000 μg / g, solute being pyridine, and solvent being a 1:1 volume ratio of toluene and isooctane). Shake at 150 rpm for 24 h in a 30℃ constant temperature water bath shaker until adsorption equilibrium is reached. Filter to separate the adsorbent, and determine the basic nitrogen content in the filtrate using the SH / T 0162-1992 indicator method. Calculate the static saturated adsorption capacity using the following formula.

[0034]

[0035] In the formula: Q is the static saturated adsorption capacity (mg / g); C0 is the basic nitrogen concentration before adsorption (μg / mL); C e V represents the alkaline nitrogen concentration after adsorption equilibrium (μg / mL); V is the oil sample volume (mL); and m is the adsorbent mass (g).

[0036] The test results are shown in Table 2.

[0037] Table 2

[0038] As shown in Table 2 above, Examples 2 and 3 exhibited the highest static adsorption capacity, far superior to Comparative Examples 4 and 5. Among the comparative examples, Comparative Example 4 performed the worst, indicating that without template orientation and TEOS network fixation, quaternary ammonium salt pillars alone, while increasing interlayer spacing, could not form size-matched, highly efficient adsorption sites. Comparative Examples 1 and 2 were significantly higher than Comparative Example 4, indicating that retaining either the template or TEOS could still produce some adsorption enhancement, but both were far lower than Example 2, proving that template pre-adsorption and TEOS cross-linking curing were both indispensable. Comparative Example 3 was far lower than Comparative Examples 1 and 2, indicating that aluminic acid washing not only affected the pore structure but also directly participated in the adsorption of basic nitrogen molecules through Lewis acid sites introduced by the aluminum pillars.

[0039] 1.3 Dynamic Penetration Test 10g of adsorbent formulation was packed into a stainless steel fixed adsorption column with an inner diameter of 10mm and a bed height of approximately 20cm. Simulated oil containing 500μg / g of basic nitrogen (pyridine as the solute) was used as the raw material, and the adsorption was carried out at 30℃ at a rate of 2mL / min (space velocity approximately 1.5h). -1 The flow rate is from top to bottom through the adsorption bed. After each certain volume of oil sample is treated, a sample is taken, and the outlet alkaline nitrogen concentration is determined according to SH / T 0162-1992. The breakthrough point is defined as when the outlet alkaline nitrogen concentration reaches 10% of the inlet concentration. The corresponding cumulative throughput (in terms of bed volume BV) at this point is the breakthrough bed volume (BV). The breakthrough adsorption capacity is calculated using the following formula:

[0040] In the formula: Q b Ct is the breakthrough adsorption capacity (mg / g); C0 is the inlet alkaline nitrogen concentration (μg / mL); Ct is the outlet alkaline nitrogen concentration at time t (μg / mL); Vb is the breakthrough cumulative volume (mL); m is the adsorbent mass (g).

[0041] The test results are shown in Table 3.

[0042] Table 3

[0043] As shown in Table 3 above, Examples 2 and 3 exhibit excellent dynamic penetration performance. Comparative Example 4 has the lowest penetration capacity because it lacks the molecular imprinting effect and the matching-locking synergistic effect of the TEOS confined network, allowing the adsorbent to penetrate rapidly in the dynamic flow field. Comparative Examples 3 and 5 are also significantly lower than Example 2. The low penetration capacity of Comparative Example 3 is attributed to incomplete defluorination, leading to F... - Corrosion of the equipment also interfered with the quaternary ammonium salt pillar. The low penetration capacity of Comparative Example 5 is attributed to the increased acidity of the activated clay after sintering and activation, but its single pore size, which is far inferior to the porous structure and synergistic adsorption effect of the clay-diatomite composite powder.

[0044] 1.4 Selectivity Test A simulated oil containing a mixture of basic nitrogen compounds was prepared: pyridine (pKb=8.75), quinoline (pKb=9.15), and aniline (pKb=9.30), with each component having a basic nitrogen concentration of 200 μg / g. Adsorption was performed according to the static adsorption test procedure, and the concentrations of each component before and after adsorption were measured. The selectivity coefficient (α) for pyridine relative to aniline was calculated.

[0045] In the formula: Q is the adsorption capacity of each component (mg / g); C_ e The concentrations of each component at adsorption equilibrium are expressed in μg / mL.

[0046] The test results are shown in Table 4.

[0047] Table 4

[0048] As shown in Table 4 above, pyridine and quinoline are typical basic nitrogen impurities in the catalytic feedstock. Example 2 showed a selectivity coefficient of 3.1 for pyridine, significantly higher than Comparative Examples 1 and 2. Comparative Example 1 had the lowest selectivity, demonstrating that the pyridine template formed a cavity that specifically recognizes the template molecule through molecular imprinting. Omitting the template resulted in the loss of the "size-matching" recognition ability, and adsorption mainly relied on non-specific physical adsorption and ion exchange. Although Comparative Example 2 showed higher selectivity than Comparative Example 1, it was still lower than Example 2, indicating that TEOS crosslinking "fixed" the configuration of the template molecule within the bentonite layers. The cavities left after extraction remained intact due to the rigid support of the Si-O-Si network. Comparative Example 5 showed higher selectivity than Comparative Examples 1, 2, and 4, but not as high as Example 2. This indicates that the diatomaceous earth component in the activated composite powder A provided mesopores of a certain size, contributing to the size sieving effect.

[0049] 1.5 Regeneration Performance Test The adsorbent after the breakthrough test was regenerated under the low-temperature solvent extraction conditions in step S4: extraction was performed three times at 50°C using a mixed solvent of anhydrous ethanol and deionized water (volume ratio 2:1), each time for 45 min. Then, it was dried under the vacuum stepwise drying conditions of Example 2. After regeneration, the dynamic breakthrough test was repeated, the regenerated breakthrough adsorption capacity was calculated, and compared with the original breakthrough adsorption capacity to calculate the regeneration rate.

[0050] The regeneration test was repeated three times to evaluate the stability of the adsorbent during recycling.

[0051] The test results are shown in Table 5 below.

[0052] Table 5

[0053] As shown in Table 5 above, after three regeneration cycles, Example 2 still maintained a regeneration rate of 89.5%, which is significantly better than Comparative Example 3, which had the lowest regeneration rate because of the residual F. - During the regeneration process, the material redeposits, clogging the pores and covering the active sites. The regeneration rates of Comparative Examples 4 and 5 were both lower than those of Example 2. Comparative Example 4 formed highly efficient recognition sites, but the hydrophobic environment provided by the quaternary ammonium salt pillar made the regeneration extraction process relatively easy. In Comparative Example 5, the absence of activated composite powder A reduced the strong adsorption of basic nitrogen by the hierarchical porous structure, and the basic nitrogen adsorbed on the surface was more easily removed by solvent extraction, but its initial adsorption capacity was low.

[0054] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a high-nitrogen-content denitrification adsorbent formulation, characterized in that, Includes the following steps: S1. After kneading white clay and diatomaceous earth with dilute acid and deionized water, they are calcined and activated at 300~400℃ to obtain activated composite powder A. S2. Disperse sodium-based bentonite in deionized water to prepare a 5-15 wt% slurry, and add fluorosilicic acid to carry out a pillaring reaction. After the reaction, fluoride ions were removed by a two-step method of aluminic acid washing and deionized water washing, and aluminum pillar components were introduced simultaneously. Each washing was carried out using a pulping-pressure filtration cycle process until the fluoride ion concentration in the washing liquid was ≤100ppm, and aluminum / fluorosilicic acid composite pillar bentonite filter cake was obtained. S3. The filter cake obtained in step S2 is redispersed in deionized water to prepare a slurry of 5-15 wt%. Alkaline nitrogen template molecules are added sequentially for pre-adsorption, followed by the addition of quaternary ammonium salt for organic pillaring, and then TEOS is added for hydrolysis and condensation under weakly alkaline conditions. The mixture is then filtered, washed with hot water, and dried under low-temperature vacuum to obtain modified bentonite B. S4. Mix modified bentonite B with activated composite powder A, add neutral silica sol as a binder, add deionized water to adjust to a state suitable for extrusion, extrude into strips, and after molding, first remove template molecules by low-temperature solvent extraction, and then dry in steps under vacuum to obtain the adsorbent formulation.

2. The preparation method according to claim 1, characterized in that, The mass ratio of white clay to diatomaceous earth in step S1 is (2~4):1; The dilute acid is dilute sulfuric acid, with a concentration of 2-5%, and the amount of dilute sulfuric acid added is 3-8% of the total mass of the clay and diatomaceous earth. The amount of deionized water added is 15-25% of the total mass of the clay and diatomaceous earth.

3. The preparation method according to claim 1, characterized in that, The concentration of fluorosilicic acid in step S2 is 15-25%, and the amount added is 10-20% of the dry weight of sodium-based bentonite. The reaction temperature is 60~90℃, and the reaction time is 2~6h.

4. The preparation method according to claim 1, characterized in that, The aluminate washing in step S2 is specifically as follows: use an aluminum sulfate solution with a concentration of 0.5~2.0%, and adjust the pH to 2.5~3.5 with dilute sulfuric acid. The liquid-solid ratio during washing is (4~6):1, and the stirring time is 30~60 min. Then, wash with deionized water with a liquid-solid ratio of (4~6):1 and a stirring time of 10~20 min. Wash 2~3 times.

5. The preparation method according to claim 1, characterized in that, The basic nitrogen template molecule mentioned in step S3 is pyridine; The amount of template molecule used is 2-4% of the dry weight of bentonite, and pre-adsorption is carried out by stirring at room temperature for 30-60 minutes. The quaternary ammonium salt is hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride; The amount of the quaternary ammonium salt is 8-15% of the dry weight of bentonite, and the mixture is heated to 50-70℃ and stirred for 1-3 hours to form an organic pillar.

6. The preparation method according to claim 1, characterized in that, The amount of TEOS used in step S3 is 5-15% of the dry weight of bentonite. After adding TEOS, the pH of the slurry is adjusted to 7.5-8.5 with dilute ammonia water, and the mixture is stirred at 40-60℃ for 2-6 hours for hydrolysis and polycondensation.

7. The preparation method according to claim 1, characterized in that, The hot water washing mentioned in step S3 specifically involves washing the pulp with hot water at 40~80℃ 1~3 times, with a liquid-to-solid ratio of (3~6):1; Drying is performed under vacuum at 40~80℃.

8. The preparation method according to claim 1, characterized in that, The mass ratio of modified bentonite B to activated composite powder A in step S4 is (3~6):1; The neutral silica sol has a solid content of 20-40%, a pH of 6.5-7.5, and is used in an amount of 1-5% of the total mass of the mixed powder.

9. The preparation method according to claim 1, characterized in that, The specific steps for removing template molecules by low-temperature solvent extraction in step S4 are as follows: the extruded material is immersed in a mixed solvent of anhydrous ethanol and deionized water, and extracted by stirring at 40-60°C 2-4 times, each time for 30-60 minutes, until template molecules are no longer detectable in the extract.

10. The preparation method according to claim 1, characterized in that, The vacuum stepwise drying described in step S4 specifically involves drying at 80~100℃ and at atmospheric pressure or -0.02~-0.04MPa for 0.5~1h. The second step involves drying at 100~120℃ and a vacuum of -0.08~-0.095MPa for 1~2 hours.